The Usage of Medical Mask During Brisk Walking Increases Salivary Cortisol Levels and Has A Negative Correlation to Physical Fitness (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Most health organizations recommend that people should wear masks when conducting outdoor physical activities, including exercise, during the COVID-19 pandemic. This study aimed to determine the effect of using a medical mask during brisk walking on salivary cortisol levels and its correlation with physical fitness. The study used experimental, analytical, and quantitative methodologies. Twenty-eight male subjects, aged 17-25 with a normal BMI, participated in this study. The measured data were salivary cortisol hormone levels and physical fitness index after performing brisk walking with and without using a medical mask. Salivary cortisol levels were measured after carrying out exercise using the ELISA and Delta Biologicals Salivary Cortisol kit. Physical fitness was evaluated using the Harvard Step-Up Test. Data analysis was conducted using the Wilcoxon test. A correlation analysis was performed to examine the relationship between the physical fitness index and changes in cortisol levels. After using a medical mask, the average cortisol level was 23.53 ng/mL, higher than without using a medical mask, which was 11.35 ng/mL (p=0.000). The correlation test results showed a significance value of 0.029 and a Pearson Correlation value of -0.414. Physical fitness correlated negatively with increased salivary cortisol levels during brisk walking using a medical mask. Medical mask is an important preventive measure in high-risk situations for airborne disease transmission. However, alternative safety measures may be more appropriate to be applied during moderate-intensity physical exercises, such as choosing outdoor locations with safe social distancing.